Measles virus and its biology - Fraser, Kenneth Boyd; Martin, S. J. (Samuel John), 1936- (Experimental virology., 1978)
Measles Virus and Its Biology deals with the biological and clinical problems of the viral disease, measles. This book also describes the behavior of the measles virus in terms of its immunological, biochemical, or molecular-biological aspects. The authors review the epidemiology and pathogenesis of measles and discuss how the virus flourishes and mobilizes in the human body through a close association with leukocytes and lymphoid organs. Biological characters and genetic markers of the virus can serve to separate different isolates of the measles virus from one another. Radioactive labeling t.